PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP PENINGKATAN HASIL BELAJAR SISWA MATERI IPA - Puja Windari; Mochamad Guntur (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan Univers, 2023)
The objects around us have unique properties and characteristics. By understanding the properties of objects, we can properly study the natural phenomena that occur around us. Even though there are only three forms of matter, all three of them can experience changes in form in different ways. This study aims to assess how elementary school kids learn utilizing the Project Based Learning (PJBL) paradigm in the learning process of changing the shape of objects in elementary schools. The Independent Sample T-Test employed as a research approach in this study the results of the research show that each object has a different material in its composition. With different calculation since the value is more than 0.05 and there is no difference in the findings and Sig between the experimental class and the control class, it may be concluded that the data are not different. Differences in the constituent materials cause the properties and shape of objects to change due to heating, combustion, temperature changes, rust, and decay. The results of the study confirm that the use of the PJBL model in material changes in the shape of objects can raise the standard of instruction in the control and experimental classes and provide a more meaningful learning process for students.